Community Participation in the Selection of Nias Regent Candidates in Biouti Village, Idanogawo District, Nias Regency in 2020 - Arya Kusuma B, Doddie; Wirasman Gea (Journal of Law, Politic and Humanities, 2022)
This study aims to find out: (1) What is the level of community participation in selecting the candidate for Nias Regent in Biouti Village, Idanogawo District, Nias Regency? (2) What are the obstacles faced by voters in choosing a candidate for Nias Regent in Biouti Village, Idanogawo District, Nias Regency? (3) What solutions are given to overcome the problem of lack of community participation in the election of candidates for Nias Regent in Biouti Village, Idanogawo District, Nias Regency? . The research method used in this research is descriptive-qualitative which is generally carried out with the aim of systematically describing the facts and characteristics of the object or subject that are examined appropriately. Data collection techniques were carried out through in-depth observations (interviews) with informants to obtain the information needed. The collected data was then analyzed using descriptive-qualitative analysis. Based on the results of the study, several results were obtained. (1) How the level of community participation in selecting the Nias Regent candidate in Biouti Village, Idanogawo District, Nias Regency has decreased greatly due to public distrust of the Nias Regent candidate. (2) What obstacles faced by voters in choosing a candidate for Nias Regent in Biouti Village, Idanogawo District, Nias Regency, were due to human resources, candidate background, past trauma, level of public awareness, intimidation, voter list determination, and money . politics . (3) What is the solution given to overcome the problem of lack of public participation in the election of the Nias Regent candidate in Biouti Village, Idanogawo District, Nias Regency is to provide political education, especially to novice voters, the role of the media, political parties, increasing awareness, fairness, collecting voter list data , and choose from conscience.